4/x+3 -3/x-2

IF equation is 4/x+3 = -3/x-2

4/x+3 = -3/x-2

Multiply both sides by x:

4+3x = -3-2x

Add 2x-4 to both sides:

5x = -7

x = -7/5

4/x+3 -3/x-2

Tutors, please sign in to answer this question.

Westford, MA

IF equation is 4/x+3 = -3/x-2

4/x+3 = -3/x-2

Multiply both sides by x:

4+3x = -3-2x

Add 2x-4 to both sides:

5x = -7

x = -7/5

Merced, CA

Combine like terms: ( 4/x - 3/x ) + (3 - 2).

When simplified: 1/x + 1.

Romina A.

Knowledgeable tutor in Spanish, Biology, Anatomy & Physiology and Math

Harrison, NJ

5.0
(168 ratings)

Janet K.

Teaching Assistant and retired Engineer

Yonkers, NY

5.0
(7 ratings)

Dana R.

English/Math SAT PrepTutor with PhD

Lynbrook, NY

4.8
(85 ratings)

- Math Help 4850
- Math 8598
- Algebra 4552
- Math Help For College 1306
- Algebra Help 938
- Exponents 181
- Algebra 2 3150
- Trigonometry 1327
- Simplifying Expressions 131
- Algebra 1 3739

## Comments